Hodnocení finanční situace podniku a návrhy na její zlepšení - Pyskatý, Pavel (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Bakalářská práce se zabývá finanční analýzou podniku Gumotex, a.s. v období let 2005 - 2008. V práci je použita analýza absolutních ukazatelů, rozdílových ukazatelů, poměrových ukazatelů a analýza soustav ukazatelů. Použitím těchto metod je dosaženo cíle, a to zhodnocení finanční situace podniku Gumotex, a.s. Přínosem podniku jsou tedy vyvozené závěry a doporučení pro zlepšení finanční situace.

This bachelor´s thesis deal with financial analysis company Gumotex, a.s. during the years 2005 - 2008. There is used analysis absolute indicators, distance indicators, ratio indicators and analysis system indicators in work. By using those methodsis achieved purposes, namely evaluation of financial situation company Gumotex, a.s. Contribution company are constructive findings and recommendation for improvement financial situation.
Evaluation of the Financial Situation in the Firm and Proposals to Improvement
Keywords: Finanční analýza; účetní výkazy; SWOT analýza; horizontální analýza; vertikální analýza; likvidita; zadluženost; aktivita; rentabilita; provozní ukazatele; Z-scóre; index IN; Rychlý test.; Financial analysis; accounting statements; SWOT analysis; horizontal analysis; vertikal analysis; liquidity; indebtedness; activity; profitability; operating indicator; Z-score; IN index; Quicktest.